Drug assumption and awareness about adverse drug reactions. The right to know. The case of the bone-modyfing agents: a systematic review - Mauceri, Rodolfo; Arduini, Sonia; Coppini, Martina; Bazzano, Monica; Trujillo, Isabel; Campisi, Giuseppina (Frontiers in Oral Health, 2024)
IntroductionMedication-related osteonecrosis of the Jaw (MRONJ) is an adverse drug reaction that affects the mandible and maxilla of patients exposed to BMA and AA therapies, causing the progressive destruction and death of bone. To date, oral health preventive measures remain the most effective strategy to reduce MRONJ incidence, and, in this sense, the major goal is to diagnose, treat, and eradicate any oral diseases that could compromise oral health. The present systematic review aims to investigate the awareness of MRONJ among patients assuming BMAs.MethodsA systematic literature search was performed, selecting studies that concern the awareness of patients of the risk of MRONJ.ResultsSix studies were included in this review. In total, 483 patients were evaluated. Of the 483 included patients, 391 were not aware of the possibility of MRONJ onset (391/483, 81%) and 92 were aware of it (92/483, 19%).DiscussionThe problem of patient's lack of awareness with respect to MRONJ risk presents different layers of complexity (“what?”, “who?”, “where?”, “when?” and “why?”). Among its causal factors, there are an inadequate level of communication with patients and the lack of collaboration between healthcare professionals, which is related to an individualistic view of liability and deontological duties. MRONJ is a drug adverse reaction that can greatly affect the quality of life of patients if not promptly diagnosed and treated. Therefore, patients must be fully aware of the risks of adverse and the importance of preventive measures, which imply effective and exhaustive communication by each member of the multidisciplinary team. Effective teamwork and collaborative care should be promoted to positively impact patients' awareness.